2017
DOI: 10.1111/nph.14734
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulation of TERMINAL FLOWER 1 causes the unique vernalisation response in an arctic woodland strawberry accession

Abstract: Vernalisation requirement is an agriculturally important trait that postpones the development of cold-sensitive floral organs until the spring. The family Rosaceae includes many agriculturally important fruit and berry crops that suffer from crop losses caused by frost injury to overwintering flower buds. Recently, a vernalisation-requiring accession of the Rosaceae model woodland strawberry (Fragaria vesca) has been identified in northern Norway. Understanding the molecular basis of the vernalisation requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 56 publications
2
28
0
Order By: Relevance
“…RiTFL repression may have favoured early flowering in this trial, and plants developed more reproductive buds before entering recess. This agrees with the results of [15], who demonstrated that low temperatures are necessary to suppress TFL1 in Fragaria vesca, enabling the plants to induce flowering.…”
Section: Cultivarsupporting
confidence: 92%
See 2 more Smart Citations
“…RiTFL repression may have favoured early flowering in this trial, and plants developed more reproductive buds before entering recess. This agrees with the results of [15], who demonstrated that low temperatures are necessary to suppress TFL1 in Fragaria vesca, enabling the plants to induce flowering.…”
Section: Cultivarsupporting
confidence: 92%
“…Vernalisation, the process by which low temperatures favour inception of the reproductive stage [14], is an adaptation mechanism to temperate climates in some species which require a cold period during plant development before being receptive to another signal for floral induction [15,16]. In the cultivar 'Heritage', the need for vernalisation in seasonal shoots may explain the differences in fruiting traits in different climatic environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to molecular studies, seasonal cycling of FvTFL1 mRNA expression at the shoot apical meristem causes typical seasonal flowering habit of woodland strawberry (Koskela et al, 2012(Koskela et al, , 2017. In LDs of summer, high FvTFL1 mRNA level maintains the vegetative apical meristem, while the downregulation of the…”
Section: Molecular Mechanisms Of Flowering Time Control Are Emerging mentioning
confidence: 99%
“…Whole genome resequencing of FIN12 accession was carried out at DNA Sequencing and Genomics Laboratory, Institute of Biotechnology, University of Helsinki, Finland using Illumina NextSeq 500 sequencer. Library preparation, pairend sequencing (150 + 150 bp), and the alignment of the sequencing reads on the F. vesca H4 reference genome v4.1 (Edger et al, 2018) was carried out as described earlier (Koskela et al, 2017). Sequencing data is stored at NCBI Short Read Archive (https://www.ncbi.nlm.nih.gov/sra) under the accession number XXXXXX.…”
Section: Whole Genome Resequencing Of Fin12 and Data Analysismentioning
confidence: 99%